Chapter Conclusion - Haggett, Ali (Springer Nature, 2015)
Statistically, women appear to suffer more frequently from depressive and anxiety disorders, featuring more regularly in primary care figures for consultations, diagnoses and prescriptions for psychotropic medication. This has been consistently so throughout the post-war period with current figures suggesting that women are approximately twice more likely to suffer from affective disorders than men. However, this book suggests that the statistical landscape reveals only part of the story. Currently, 75 per cent of suicides are among men, and this trend can also be traced back historically to data that suggests this has been the case since the beginning of the twentieth-century. This book suggests that male psychological illness was in fact no less common, but that it emerged in complex ways and was understood differently in response to prevailing cultural and medical forces. The book explores a host of medical, cultural and social factors that raise important questions about historical and current perceptions of gender and mental illness.